SERIES: ECONOMICS APPLIED TO PROCESS ENGINEERING (PART 6) MANAGEMENT OF RELEVANT COSTS AND INCOME IN THE SHORT-TERM ECONOMIC ANALYSIS: DO OR BUY DECISION - Porlles L., José (2006)
In the context of the continuous improvement of the chemical process industries, the cost of key raw materials or process inputs are receiving increased attention. Companies are heavily engaged in efforts to reduce costs through backward integration into manufacturing of materials. The purpose of this article is to establish or clarify the methodology of economic analysis in how to assess and develop the relevant information to make appropriate decisions for Make or Buy.